Forget what you know [large type] - Dodd, Christina (Thorndike Press large print basic, 2023)
"A car is pulled from the bottom of the lake. The driver has been shot in the back of the head and no other bodies are found. Only the legendary Dragon's Heart remains inside. When it rises to the surface, greedy collectors from around the world gather. They'll stop at nothing to gain possession of the priceless artifact. Zoey Phoenix remembers nothing about her early childhood; her mother's desire to leave those years behind never worried her until Zoey is almost killed in a hit and run and, days later, her mother disappears. Zoey has no idea who tried to murder her or why, but she's determined to unravel the dangerous truths of her past before they claim her future"--